Analytical Study of Crude Oil Price Shocks in the Global, Market Reasons and Result - سلمان محمد صالح; حميد عبد الحميد عبد الهادي (Journal of Economics and Administrative Sciences, 2018)
The global oil market is one of the most important markets in the world and occupies especially for countries consuming and producing countries, and the status of understanding of the mechanism for determining prices in the market help to stand on many factors affecting oil demand and supply of oil and geopolitical factors, climate and alternative sources of energy .. etc. factors, and that the main objective of the research is to study the causes and results left behind by the oil price shocks in the world market, and the movement of these factors be through a cycle of energy that explain the strength of competition between these factors and their effects on prices, when demand increases evolution Large image leads to significant increases in prices because of the oil supply is flexible and needs a period of time to adjust and balance again in the oil market generator that imbalance in the energy cycle evolution (positive shock), when falling oil demand in front of increase oil supply, the balance is collapsing because of satiety The oil market witnessed many shocks in its prices from 1973 to 2014, sometimes negative and sometimes positive, and the factors affecting each shock vary. time history, vary Nes The impact of each factor affecting the market in each shock and this complicates the possibility to predict positive negative price shocks, as well as in the difficulty of determining the length of time separating the shock and other.